2020
DOI: 10.1101/2020.05.08.082784
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

E2F4 as a single multifactorial target against Alzheimer’s disease

Abstract: Alzheimer's disease (AD) has a multifactorial etiology, which requires a single multi-target approach for an efficient treatment. We have focused on E2F4, a transcription factor that regulates cell quiescence and tissue homeostasis, controls gene networks affected in AD, and is upregulated in the brain of Alzheimer's patients and of APP/PS1 and 5xFAD transgenic mice. E2F4 contains an evolutionarily-conserved Thr-motif that, when phosphorylated, modulates its activity, thus constituting a potential target for i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(14 citation statements)
references
References 98 publications
(215 reference statements)
8
6
0
Order By: Relevance
“…Neuronal expression of murine E2F4DN-myc in transgenic mice leads to slowdown of Aβ accumulation in 5xFAD mice at 3-6 months of age [19]. Consistently, we found that the intravenous administration of AAV-hE24DN in 1.5-monthold h5xFAD mice leads to a time-dependent reduction of Aβ production in the hippocampus (Fig.…”
Section: Systemic Delivery Of He2f4dn the Aavphpb Vector Reduces Aβ Levels And Plaques In H5xfad Micesupporting
confidence: 84%
See 4 more Smart Citations
“…Neuronal expression of murine E2F4DN-myc in transgenic mice leads to slowdown of Aβ accumulation in 5xFAD mice at 3-6 months of age [19]. Consistently, we found that the intravenous administration of AAV-hE24DN in 1.5-monthold h5xFAD mice leads to a time-dependent reduction of Aβ production in the hippocampus (Fig.…”
Section: Systemic Delivery Of He2f4dn the Aavphpb Vector Reduces Aβ Levels And Plaques In H5xfad Micesupporting
confidence: 84%
“…As in our previous study using transgenic mice that express mouse E2F4DN-myc in neurons [19], AAV-hE2F4DN-myc vector administration did not trigger detectable adverse effects. Similar body weight gain was observed during the whole life span in WT mice subjected to systemic delivery of AAV-hE2F4DN-myc when compared with WT mice treated with a control AAV.PHP.B vector expressing EGFP under the control of the hSyn1 promoter control (AAV-EGFP) (Fig.…”
Section: He2f4dn-myc Expression In Cortical Neurons From Wt Mice Does Not Trigger Adverse Effectssupporting
confidence: 80%
See 3 more Smart Citations